PENGEMBANGAN MEDIA PETA TEMATIK DENGAN MATERI SEJARAH LOKAL ALUN-ALUN KOTA DI SMAN 1 TUBAN - Khakim, Mochammad Nurfahrul Lukmanul; Primanggalang, Kautsar Ranggi; Yuliati, Yuliati; Surya, Riza Afita (Sejarah dan Budaya: Jurnal Sejarah, Budaya, dan Pengajarannya, 2022)
This research begins by looking at the learning problems that occur in class XI IPS 1 at SMAN Tuban, namely the lack of motivation and student learning outcomes, then conducting a needs analysis and selecting media development according to the problems that occur. The thematic map media development that utilizes the Google Maps application uses a development model from Lee & Owen. The results of the validation show: 1) Material validator with a percentage of 85.41 percent with "valid" criteria, 2) Media validator with a percentage of 86.86 percent with "valid" criteria, 3) Increasing learning motivation, after comparing before and after applying thematic maps show a difference of 24 percent, with the criteria "motivated", 4) Improve student learning outcomes, the comparison between pretest and post-test shows a difference of 21 percent, with the criteria "satisfactory". Based on the research results, it can be concluded that thematic map media using the Google Maps application can increase student motivation and learning outcomes.